Quantitative Estimation of Naproxen in Bulk Sample and Tablet Formulation Using Niacinamide as Hydrotropic Solubilizing Agent - Maheshwari, R.K.; Dubey, Anshuman (Asian Journal of Chemistry, 2010)
In the present investigation, 2.0 M niacinamide (an economic solubilizing agent) was employed to solubilize poorly water-soluble antiinflammatory drug, naproxen for its titrimetric analysis. The proposed method is new, environmentally friendly, accurate and reproducible. Accuracy, reproducibility and precision of the proposed method were validated statistically.